Discovery of a Novel Species Infecting Goats: Morphological and Molecular Characterization of Babesia aktasi n. sp. - Ozubek, Sezayi; Ulucesme, Mehmet Can; Aktas, Munir (Mdpi, 2023)
A novel Babesia sp. infecting goats was discovered based on the molecular findings obtained in the current study, which was conducted in the Mediterranean region of Turkiye. The goal of this study was to isolate this species of Babesia (Babesia sp.) infecting goats in vivo and to assess the genetic and morphological characterization of the parasite. To identify the animal naturally infected with Babesia sp. and isolate the parasite from this animal, field studies were conducted first, and genomic DNA were extracted from blood samples taken from goats (n = 50). The Theileria, Babesia, and Anaplasma species were identified using a nested PCR-based reverse line blotting (RLB) method. The study included one goat that was determined to be infected with Babesia sp. (single infection) in RLB for in vivo isolation. A blood smear was prepared to examine the parasite's morphology, but it was found to be negative microscopically. Following that, a splenectomy operation (to suppress the immune system) was performed to make the parasites visible microscopically in this animal. Parasitemia began after splenectomy, and the maximum parasitemia was determined to be 1.9%. The goat displayed no significant symptoms other than fever, loss of appetite, and depression. During a period when parasitemia was high, blood from this goat was inoculated into another splenectomized goat (Theileria-Babesia-Anaplasma-Mycoplasma spp. free). On the third day of inoculation, 10% parasitemia with high fever was detected in the goat, and on the fourth day, the goat was humanely euthanized due to severe acute babesiosis symptoms. Except for mild subcutaneous jaundice, no lesions were discovered during the necropsy. According to the microscopic measurement results, ring, double pyriform, spectacle-frame-like, and line forms were observed, and it was observed to be between 1.0-2.5 mu m (1.38 +/- 0.17 to 0.7 +/- 0.21-all forms). A phylogenetic analysis and sequence comparison using the 18S rRNA and cox1 genes revealed that this species is distinct from the small ruminant Babesia species (18S rRNA 92-94%, cox1 79-80%) and has the highest similarity to Babesia sp. deer, which has been reported in deer. Furthermore, it was determined to resemble B. venatorum, B. divergens, Babesia sp. FR1 and Babesia sp. MO1 species, all of which are zoonotic. Additional research is needed to clarify the clinical status of this parasite in goats and other hosts (mountain goat, sheep, calf).
Keywords: Babesia; goat; morphology; phylogenetic analysis; sequence comparison